Efficacy and safety of very early rehabilitation for acute ischemic stroke: a systematic review and meta-analysis - Lou, Ying; Liu, Zhongshuo; Ji, Yingxiao; Cheng, Jinming; Zhao, Congying; Li, Litao (Frontiers in Neurology, 2024)
Background Early rehabilitation after acute ischemic stroke (AIS) contributes to functional recovery. However, the optimal time for starting rehabilitation remains a topic of ongoing investigation. This article aims to shed light on the safety and efficacy of very early rehabilitation (VER) initiated within 48 h of stroke onset. Methods A systematic search in PubMed, Embase, Cochrane Library, and Web of Science databases was conducted from inception to January 20, 2024. Relevant literature on VER in patients with AIS was reviewed and the data related to favorable and adverse clinical outcomes were collected for meta-analysis. Subgroup analysis was conducted at different time points, namely at discharge and at three and 12 months. Statistical analyses were performed with the help of the Meta Package in STATA Version 15.0. Results A total of 14 randomized controlled trial (RCT) studies and 3,039 participants were included in the analysis. VER demonstrated a significant association with mortality [risk ratio (RR) = 1.27, 95% confidence interval (CI) (1.00, 1.61)], ability of daily living [weighted mean difference (WMD) = 6.90, 95% CI (0.22, 13.57)], and limb motor function [WMD = 5.02, 95% CI (1.63, 8.40)]. However, no significant difference was observed between the VER group and the control group in adverse events [RR = 0.89, 95% CI (0.79, 1.01)], severity of stroke [WMD = 0.52, 95% CI (−0.04, 1.08)], degree of disability [RR = 1.06, 95% CI (0.93, 1.20)], or recovery of walking [RR = 0.98, 95% CI (0.94, 1.03)] after stroke. Subgroup analysis revealed that VER reduced the risk of adverse events in the late stage (at three and 12 months) [RR = 0.86, 95% CI (0.74, 0.99)] and degree of disability at 12 months [RR = 1.28, 95% CI (1.03, 1.60)], and improved daily living ability at 3 months [WMD = 4.26, 95% CI (0.17, 8.35)], while increasing severity of stroke during hospitalization [WMD = 0.81, 95% CI (0.01, 1.61)]. Conclusion VER improves activities of daily living (ADLs) and lowers the incidence of long-term complications in stroke survivors. However, premature or overly intense rehabilitation may increase mortality in patients with AIS during the acute phase. PROSPERO registration number: CRD42024508180. Systematic review registration This systematic review was registered with PROSPERO (https://www.crd.york.ac.uk/PROSPERO/). PROSPERO registration number: CRD42024508180.